Digital ecosystem models in business: challenges of management theory and practice - T. V. Gudkova; G. Yu. Kuznetsov (Модернизация, инновация, развитие, 2022)
Purpose: this article is aimed at identifying the economic effects arising out of the integration of companies within the framework of the digital business ecosystem.Methods: the article is based on the concept of the evolution of organizational systems in the context of the ecosystem approach, as well as on the provisions of the economic theory of network effects. The main methods of scientific research are represented by the structural- logical, bibliographic, computational-constructive and graphic method.Results: the review of current publications related to the issue being considered showed that in the era of the Internet and digital technologies, the main factor of economic benefit is the network effect or the demand scale effect, as well as the fact that a new source of competitive advantage and market dominance pertains to the ecosystem of users. It is revealed that the strategy of unification within the framework of digital business ecosystem allows companies to provide additional value for customers and meet the utmost number of their needs. Due to the analysis presented in this research, other economic effects, as well as the risks of integration strategies with the digital business ecosystem based on the example of the market of mobile applications designed to pay for fuel in Russia have been identified.Сonclusions and Relevance: currently, companies are increasingly adopting an ecosystem-oriented format of work when creating their business models, which allows them to scale their business at low cost and minimal investments, enter new markets, increase the customer's lifecycle and gain additional profit. Digital technologies bring the participants of business ecosystems to a new level of interaction thus leading to the reduction of barriers which prevent the synergetic effects from partner integration. The empirical analysis in the study also exposed potential risks of cooperation with the digital business ecosystem, as well as an alternative way of the organization's development strategy, which allows creating its own digital ecosystem in the future. The results have been tested in the process of improving the integration strategies of the company "Benzuber" and despite the fact that the analysis has a number of limitations, the findings might have practical implications for optimizing the development strategies of other companies.